Influence of Static Tensile Testing on the Deformation Behavior of Al-4% Cu Alloy Containing Micro- and Nanoparticles; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Khrustalyov A. Anton (2016, 2016)
Title screen